The division of labor and the market for organizations - Assar Lindbeck; Dennis J. Snower (Center for Economic Studies and ifo Institute (CESifo), 2000)
The paper examines of the division of labor within firms. It provides an explanation of the pervasive observed changes in work organisation away from the traditional functional departments and towards multi-tasking and job rotation. Whereas the exsisting literature on the division of labour within firm emphasizes the returns from specialisation and the need for coordination of the work of different workers, the present analysis focuses on the returns from multi-tasking, which is shown to arose from informational and technological complementaries among task as well as from the exploitation of the versality of human capital. The paper also explores how the move towards multi-tasking can effect the labor market and the distribution of firms across organizational forms.
Keywords: J23; J24; L23; M12; O33; 330; division of labor; specialization; multi-tasking; organization of work; technological change; information flows; Arbeitsorganisation; Reorganisation; Arbeitsteilung; Verbundvorteil; Theorie der Unternehmung; Organisationstheorie; Industrieökonomik; Arbeitsmarkt; Theorie